Like-charged protein-polyelectrolyte complexation driven by charge patches - Yigit, Cemil; Heyda, Jan; Ballauff, Matthias; Dzubiella, Joachim (The Journal of chemical physics, 2015)
We study the pair complexation of a single, highly charged polyelectrolyte (PE) chain (of 25 or 50 monomers) with like-charged patchy protein models (CPPMs) by means of implicit-solvent, explicit-salt Langevin dynamics computer simulations. Our previously introduced set of CPPMs embraces well-defined zero-, one-, and two-patched spherical globules each of the same net charge and (nanometer) size with mono- and multipole moments comparable to those of globular proteins with similar size. We observe large binding affinities between the CPPM and the like-charged PE in the tens of the thermal energy, kBT, that are favored by decreasing salt concentration and increasing charge of the patch(es). Our systematic analysis shows a clear correlation between the distance-resolved potentials of mean force, the number of ions released from the PE, and CPPM orientation effects. In particular, we find a novel two-site binding behavior for PEs in the case of two-patched CPPMs, where intermediate metastable complex structures are formed. In order to describe the salt-dependence of the binding affinity for mainly dipolar (one-patched) CPPMs, we introduce a combined counterion-release/Debye-Hückel model that quantitatively captures the essential physics of electrostatic complexation in our systems.
Keywords: chemické modely; Computer Simulation; Proteins; Salts; počítačová simulace; povrchové vlastnosti; Models, Chemical; Solvents; Electrolytes; proteiny; Static Electricity; Surface Properties; soli; elektrolyty; rozpouštědla; statická elektřina